Piano Sonata no. 3 in C major, op. 2, no. 3, published by Arnold - Beethoven, Ludwig van, 1770-1827 (composer):::Creator:::::::::::: (F. W. Arnold; Germany; Elberfeld, 2024)
Piano Sonata no. 3 in C major op. 2, no. 3, reprint by F. W. Arnold of the edition published by J. André, with plate number removed.